Development of a comprehensive model of social entrepreneurial intention formation using a quality tool - Vivek Ahuja; Asif Akhtar; O. P. Wali (Journal of Global Entrepreneurship Research, 2019)
This study attempts to arrive at the vital factors affecting social entrepreneurial intentions and establish a model with the help of the Pareto principle. In the first stage, a thorough literature review on the factors affecting social entrepreneurial intentions was conducted which revealed a number of variables that influence or are responsible for the formation of social entrepreneurial intentions. In the second stage, a quality tool 'Pareto analysis' was used to identify and propose 'vital few' factors, by applying the 80:20 rule. Lastly, the study proposes a comprehensive model of social entrepreneurial intention formation. (a) The results of this study will be helpful in further research on the subject by providing a ready literature review on the subject, (b) the model can be used by fellow researchers in related research works, and (c) the resulting appropriate factors may be inculcated in curriculum of academic programs, experiential learnings, and trainings related to social entrepreneurship.
Keywords: 650; Social entrepreneurship; Social entrepreneurial intention; Entrepreneurial intention; Pareto analysis; Theory of planned behavior